The United States Supreme Court vs. American Indian self-determination: A case study of resistance and social action - Gabrielle Ann Scott Elliott; Alberta Iron Cloud Miller (Adult Education Research Conference, 1996)
This paper examines the metaphors, labels and discourses employed by adult educators in the construction of their professional and personal identities in the rapidly changing social and institutional context of contemporary adult education. It suggests a typology for the analysis of metaphors of self-identity.